Monitoring and operation control of distributed energy resources - Lim, Desmond Chen Fan. (2009)
Continuing from the 2007/08 semester 2, FYP A1122S project, MW Optimization of Intelligent Energy Distribution System (IEDS), this project aims to improve a small energy distribution system that can operate economically by identifying the level of demand loads. This is termed the Intelligent Energy Distribution System (IEDS). In the report, it will describe several vital controlling hardware components, such as the Automatic Gen-set Controller (AGC), Multi-instrument controller components, as well as circuit breakers with motorized mechanism. In order to simulate several local power generation for the system, synchronous generations with DC motors as the prime-mover have been included in IEDS. Furthermore, governors and automatic voltage regulators (AVR) were installed in it, to make it less dependent on users. These are the components which are the basic building blocks of IEDS. Software-wise, in order to obtain optimum power for the least load in IEDS, program algorithms have been written such that economic dispatch is ensured. The improvement of the Graphical User Interface (GUI) to better collates vital information from hardware like AGC and MIC aids in evaluating IEDS by employing the concept of economic dispatch into the system. This process is conducted through Modbus communication, an industry standard protocol commonly used for data communication. Thus IEDS encompasses both the hardware and software characteristics as explained above and distributes energy both intelligently and economically. There is a need for further improvement and research in order to overcome some limits of the system, which can be done by constructing a highly accurate, responsive and user friendly system for IEDS.